The Correlation Between Mothers’ Knowledge Level And Polio Immunization Coverage At Dahlia Integrated Healthcare Center Of Datarajan - adi saputra; Vicko Suswidiantoro; Fina Aulika Lestari; Diah Kartika Putri (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2025)
Polio is a dangerous contagious disease that continues to threaten children, with recent cases re-emerging in Indonesia due to low immunization coverage. A lack of maternal knowledge has been identified as one of the main barriers to the success of polio immunization programs. This study aims to analyze the correlation between mothers’ knowledge level and polio immunization coverage among children at Dahlia Integrated Healthcare Center of Datarajan Village. A quantitative cross-sectional study was conducted from February to April 2025 in Datarajan Village of Tanggamus Regency, involving 47 respondents. Data were collected using a questionnaire on mothers’ knowledge and children’s immunization status and analyzed using univariate and bivariate methods. The results showed that most mothers had a “Moderate” level of knowledge (53%), while the majority (91%) of children had received complete polio immunization. Statistical analysis revealed no significant correlation between mothers’ knowledge level and completeness of polio immunization p value 0,071. The high coverage of complete immunization despite varying knowledge levels highlights the important role of reminders provided by local midwives in ensuring immunization completion. Factors such as a child’s illness were cited as reasons for incomplete immunization. In conclusion, no significant correlation was found between mothers’ knowledge level and polio immunization coverage. The completeness of immunization was more strongly influenced by the proactive role of healthcare workers in reminding parents of immunization schedules.